Surface topography and biocompatibility of Ti-6Al-4V after Wire Electro-Discharge Machining (WEDM) / Nornisaadila Musa ...[et al.] - Musa, Nornisaadila; Saedon, J. B; Adenan, Mohd Shahriman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Ti-6Al-4V is the difficult-to-machine material commonly used for biomedical applications. The surface characteristics of the Ti-6Al-4V plays an important role in the biocompatibility and the industries. The machining of titanium is complex due to its characteristics and have limitations such as variations of chip thickness, high heat stress, high-pressure loads, and residual stress during the conventional machining process. The research presents the experimental of wire electro-discharge machining (WEDM) on Ti-6Al-4V. The research aims to characterize the surface topography of Ti-6Al-4V after WEDM process and the biocompatibility of the machined surface. The machined surface analyzed for the surface topography, elementary analysis and cell viability to observe the biocompatibility of WEDM process based on the variation of peak current, pulse-off time and wire tension. The white layer thickness of high input parameters produced a thicker layer on the machined surface. As the effect of the machining process, there is the existence of Ti, Cu, V, Zn, C, O, and Al on Ti-6Al-4V surface. The results show that the WEDM process on Ti-6Al-4V was biocompatible for medical implants as L929 cells positively active in the culture medium. The sets of input parameters for good surface characterization are 6A peak current, 2µs pulse-off time and 8N wire tension.